Implementation of Augmented Reality in Teaching Local History to Elementary Students - Arifin, Iqbal; Manda, Darman; Darmayanti, Dyan Paramitha (Universitas Sulawesi Barat, 2025)
Learning local history at the primary school level plays a crucial role in shaping students' identity, character, and cultural awareness from an early age. Through stories from the surrounding environment, students have the opportunity to recognize local wisdom values and understand social dynamics that are close to their lives. Unfortunately, history learning in schools is still primarily delivered conventionally - text-based and memorized - which often makes students less interested and not actively involved. This research aims to examine the potential of Augmented Reality (AR) technology in reviving local history learning to make it more meaningful and enjoyable for students. The research employed a literature study method and a qualitative descriptive approach, analyzing 25 sources of scientific literature published between 2006 and 2025 through content analysis techniques. The research shows that AR technology can present historical material visually, interactively, and contextually, thereby strengthening students' cognitive understanding while fostering emotional involvement in the learning process. However, the effectiveness of AR is strongly influenced by the readiness of teachers in techno-pedagogical aspects, the growing digital culture in schools, and the availability of adequate supporting infrastructure.